Extensive aircraft activity impacts subsistence areas: acoustic evidence from Arctic Alaska - Taylor R Stinchcomb; Todd J Brinkman; Davyd Betchkal (Environmental Research Letters, 2020)
Aircraft activity is expanding across Arctic Alaska, potentially changing social-ecological systems. Arctic communities report that aircraft disturb wildlife and negatively influence harvest practices and experiences. Limited data have restricted knowledge about the extent of aircraft activity over traditional harvest areas. Our objective was to use soundscape monitoring methods to document aircraft overflights around the rural subsistence-based community of Nuiqsut to inform impact mitigation processes. This study provides the first quantitative estimates of aircraft activity in rural Arctic Alaska. We deployed 20 acoustic monitoring systems in summer 2016 along travel corridors used to harvest caribou ( Rangifer tarandus ). Sound recordings captured 7465 aircraft events during peak caribou harvest season. Aircraft activity reached a median of 12 overflights per day near human development, approximately six times greater than undeveloped areas. Aircraft noise decreased incrementally with distance from human development. Given that subsistence harvesters report that aircraft startle caribou and prefer to avoid aircraft themselves, this result implies that they will need to travel farther for a successful harvest, incurring higher costs of fuel, equipment, and effort. Such costs could be prohibitive for many harvesters. Our research demonstrates that acoustic data can aid in understanding how human-to-human interactions impact social-ecological dynamics in the Arctic.